Michigan - Gregory, Josh (New York, Children's Press, 2018)
An introduction to the wildlife, history, and culture of Michigan.
Map: This is Michigan! -- Land and wildlife -- What is the terrain of Michigan like and what lives there? -- Government -- What are the different parts of Michigan's government? -- The big truth -- What represents Michigan? -- Which designs, objects, plants, and animals symbolize Michigan? -- History -- How did Michigan become the state it is today? -- Culture -- What do Michiganians do for work and fun?
Includes bibliographical references (page 46) and index.
6.6
3-6
Keywords: Michigan -- Juvenile literature; Michigan